Analogs of the spherical transform on the hyperbolic plane - Vasilyanskaya, V. S.; Volchkov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We introduce the notion of “$s$”-convolution on the hyperbolic plane $H^2$ and consider its properties. Analogs of the Helgason spherical transform on the spaces of compactly supported distributions in $H^2$ are studied. We prove a Paley –Wiener – Schwartz-type theorem for these transforms.